2012
DOI: 10.1155/2012/386962
|View full text |Cite
|
Sign up to set email alerts
|

Altered Dynamic Postural Control during Step Turning in Persons with Early-Stage Parkinson’s Disease

Abstract: Persons withearly-stageParkinson’s disease (EPD) do not typically experience marked functional deficits but may have difficulty with turning tasks. Studies evaluating turning have focused on individuals in advanced stages of the disease. The purpose of this study was to compare postural control strategies adopted during turning in persons with EPD to those used by healthy control (HC) subjects. Fifteen persons with EPD, diagnosed within 3 years, and 10 HC participated. Partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 30 publications
(49 reference statements)
2
40
0
1
Order By: Relevance
“…Postural control was analyzed before and at the completion of the study as our previous published work demonstrated it to be a sensitive motor measure in early PD [11]. Participants walked straight and turned at a 'self-selected, comfortable pace' at the designated stanchions at a right angle toward their dominant leg and then continued walking in the new direction.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Postural control was analyzed before and at the completion of the study as our previous published work demonstrated it to be a sensitive motor measure in early PD [11]. Participants walked straight and turned at a 'self-selected, comfortable pace' at the designated stanchions at a right angle toward their dominant leg and then continued walking in the new direction.…”
Section: Methodsmentioning
confidence: 99%
“…Using previously reported kinematic methods, postural control during turning was quantified as the peak distance between the center of pressure (COP) of the supporting foot and the extrapolated center of mass (eCOM) [11]. Separation of the COP and the eCOM creates the momentum necessary for successful turning.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such motor deficits commonly lead to poor performance in measures of balance and functional tasks, and have been associated with generalised deficits of attention and falls [3]. Difficulties with turning around the longitudinal axis are a common and early feature of PD, and can be present while lying recumbent [4], seated [5], standing [6][7][8][9][10][11][12][13][14][15] or walking [9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%